Utilization of the system architecture in the context of validation in the business-to-business (B2B) sector - Humpert, Lynn; Wilke, Daria; Brueggemann, Sarah; Anacker, Harald; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The European Green Deal aims to reduce global emissions by minimizing the use of resources. Early validation of products helps to reduce rework, costs and therefore resources. However, validation of complex mechatronic products is challenging due to interdependencies. Companies are applying systems engineering to meet this challenge. Current validation approaches are insufficient in the early design phases. This paper presents an approach to validation using the system architecture in the B2B sector. A machine tool and a custom built machine are presented as evaluation examples.